Te and Ru co-doped FeS2 material and preparation method and application thereof
Through the method of combining Te and Ru with ball milling and calcining, high-performance Te and Ru co-doped FeS2 materials were prepared, which solved the problems of insulation, structural instability and slow reaction kinetics of FeS2 materials, and achieved higher energy density and cyclic stability.
Patent Information
- Application Number
- CN202510104464.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-23
AI Technical Summary
As a battery positive electrode material, FeS2 has insulating reaction products, lattice structure instability, interface contact problems caused by volume expansion, and slow reaction kinetics, which affects its energy density and cycle life.
By co-doping of Te and Ru, combined with ball milling and calcining, Te and Ru co-doped FeS2 materials were prepared to improve their conductivity, structural stability and reaction kinetics.
The energy density, charge and discharge efficiency and cycle stability of FeS2 are improved, undesired volume expansion is suppressed, and the overall performance of the battery is significantly improved.
Smart Images

Figure CN119542406A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a Te and Ru co-doped FeS2 material and a preparation method and application thereof. Background Art
[0002] The replacement of liquid batteries with all-solid-state batteries is a major technological change. Compared with liquid batteries, all-solid-state batteries have higher energy density, safer working environment and broader application prospects.
[0003] The emergence of secondary rechargeable batteries has solved the problem of unusable primary battery resources and short service life. All-solid-state lithium metal batteries are currently mature energy batteries with established commercial layouts. Many researchers are committed to improving the energy density of batteries to match the current hot new energy power equipment. The most direct route is to select and modify the positive electrode to improve the energy density and cycle life of the battery. FeS2 primary batteries have long been commercialized, but they are contrary to the concepts of resource utilization and sustainable development. Irreversibility and insecurity have made them lose people's attention. However, as a positive electrode material, it is better than the mainstream Li (NiMnCo) 1 / 3 O2 (expressed as NMC) (<280 mAh g -1 ) has a higher theoretical specific capacity (894mAhg -1 ). However, liquid batteries are often affected by limited reversibility due to slow kinetics, harmful volume changes, and the insulating properties of reaction products. Similar to lithium-sulfur batteries, harmful dissolution of polysulfides may exist in lithium iron disulfide batteries, and a potential mitigation strategy may be used in solid-state batteries. In addition, FeS2 is an active material in the battery. During the redox reaction, the rearrangement of the crystal structure caused by the thermal instability of Fe and the conversion to polysulfides caused by S jointly increase the volume expansion problem of the original molecule. This harmful problem can be fundamentally alleviated by element doping substitution. Therefore, how to improve the insulating reaction products, lattice structure instability, interface contact problems caused by volume expansion, and slow reaction kinetics is a meaningful topic. Summary of the invention
[0004] In view of this, the present invention provides a Te and Ru co-doped FeS2 material and a preparation method and application thereof, aiming at improving and enhancing the electrical conductivity, volume expansion, structural stability, energy density and electrochemical conversion efficiency.
[0005] Te and S are in the same main group and have similar properties to S. However, Te as a semiconductor has higher conductivity than S (10 -7 S / m vs 10 -20S / m, and its conductivity can be further improved by doping or alloying. In addition, Te has a high valence state (such as Te 6+ ), doped in the positive electrode material helps to improve the redox potential of the material, which in turn helps to improve the energy density of the battery, and Te can form a Te-Fe-Te ordered structure with Fe to form a finer structure, which can stabilize the crystal structure and slow down the grain pulverization problem caused by the crystal structure strain of FeS2. In addition, Te is large in size, which allows it to provide a larger interlayer spacing when forming a layered material (such as FeTe), which is beneficial to the diffusion and transport of ions or molecules, thereby improving the reaction kinetics. Ruthenium (Ru) and iron (Fe) are both metal elements with the same excellent conductivity, but due to their different electronic structures and physical properties, Ru exhibits excellent electrochemical catalytic activity and thermal stability. In both fuel cells and lithium-oxygen batteries, it has shown the function of improving the charge and discharge efficiency and cycle stability of the battery.
[0006] The present invention provides a method for preparing a Te and Ru co-doped FeS2 material, comprising the following steps: S1. Premixing ferrous sulfide powder (FeS2) and tellurium ruthenium powder (Te&Ru) in an inert gas environment to obtain a premix to ensure that the two powders are fully mixed; the molar ratio of ferrous sulfide powder (FeS2) to tellurium ruthenium powder (Te&Ru) is 1-1.8:1; the tellurium ruthenium powder (Te&Ru) is a mixed powder of tellurium powder and ruthenium powder; S2, ball milling the premix; S3. The ball-milled material is calcined, and the calcined product is cooled to ambient temperature to obtain the Te-doped FeS2 material.
[0007] In step S1, in the tellurium ruthenium powder (Te&Ru), the molar ratio of tellurium powder to ruthenium powder is 1:2-2:1.
[0008] Preferably, in step S1, the molar ratio of the ferrous sulfide powder (FeS2) to the tellurium ruthenium powder (Te&Ru) is 1-1.5:1.
[0009] More preferably, in step S1, the molar ratio of the ferrous sulfide powder (FeS2) to the tellurium ruthenium powder (Te&Ru) is 1:1.
[0010] In step S1, the premix is ground using a mortar.
[0011] In step S2, a planetary ball mill is used for mechanical ball milling; the ball-to-material ratio is 3-5:1, the ball milling conditions are 350-450 rpm, and the ball milling time is 18-24 hours. The ball milling medium is zirconium oxide ball milling beads with a particle size of 3-5 mm.
[0012] In step S3, calcination is performed in a tube furnace.
[0013] In step S3, the calcination temperature is 800° C. to 950° C., and the calcination time is 10 hours to 12 hours.
[0014] <Second Aspect> The present invention also provides a Te and Ru co-doped FeS2 material prepared by the preparation method described above.
[0015] <Third Aspect> A method for preparing a Te and Ru co-doped FeS2 composite positive electrode material comprises the following steps: Step 1: In a protective atmosphere, the Te and Ru co-doped FeS2 material as described above is mixed with a sulfide electrolyte in proportion and tumble-milled; Step 2: Continue to add conductive carbon to the material of step 1 and further ball mill to obtain the Te and Ru co-doped FeS2 composite positive electrode material.
[0016] In step 1, the rolling conditions are: ball-to-material ratio 2:1-5:1; rotation speed 200-500rpm; rolling method is intermittent rolling, grinding for 0.5-1h each time, and stopping for 5-10min; a total of 8-10 times.
[0017] In step 2, the ball milling conditions are: ball-to-material ratio 2:1-5:1; rotation speed 300-500 rpm; intermittent ball milling; each ball milling is 0.5-1h, stop for 5-10min; a total of 10-20 times.
[0018] The mass ratio of the Ru and Te co-doped FeS2 material, sulfide electrolyte, and conductive carbon is: 40~50:40~50:10~20.
[0019] The sulfide electrolyte includes Li 5.5 PS 4.5 X 1.5 , Li 10 MP2S 12 , 80 Li2S·20P2S5; wherein, M is selected from at least one of Ge, Si or Sn; and X is selected from at least one of F, Cl, Br or I.
[0020] The conductive carbon is at least one of carbon fiber coated nanostructured carbon (VGCF), carbon black, conductive graphite, and carbon nanotubes.
[0021] As an embodiment of the present invention: the preparation method of the Te and Ru co-doped FeS2 composite positive electrode material comprises the following steps: Step 1, under a protective atmosphere, Te and Ru co-doped FeS2 material and sulfide electrolyte are mixed in a mass ratio of 40-50:40-50, and then rolled at a speed of 200-300 rpm for 4-10 hours at a ball-to-material ratio of 2:1-5:1; after the rolling, the ball-to-material separation is performed; Step 2: Continue to add VGCF to the material after removing the abrasive in step 1, according to the ball-to-material ratio of 2:1-5:1, and ball mill at a speed of 300-500rpm for 4-10h to obtain the Te and Ru co-doped FeS2 composite positive electrode material.
[0022] The shielding gas is argon.
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a modification method of a multi-element co-doped active material, which combines the high conductivity and high valence of Te with the excellent electrochemical catalytic activity and thermal stability of Ru through co-doping of Te and Ru, thereby comprehensively improving the energy density, charge and discharge efficiency and cycle stability of FeS2 and suppressing undesirable volume expansion.
[0024] 2. The present invention provides a Te and Ru co-doped FeS2 material for use in sulfide-based all-solid-state lithium batteries. By adopting a doping method combining ball milling and calcination, the following enhancement effects are achieved: a simple ball milling method can be used to evenly distribute the particles of FeS2, Te and Ru, and a high-energy ball milling method can cause rearrangement and exchange of atoms between crystals. Combined with the calcination method, doping atoms can be incorporated by infiltration to ensure the uniformity and stability of the size and structure of the new crystals while removing unsuccessfully doped Te and Ru elements. Comparative studies have shown that the product of a single doping method will have crystal agglomeration, uneven size, and the presence of elemental Te and Ru.
[0025] 3. The present invention also provides a Te and Ru co-doped FeS2 composite positive electrode material, wherein the composite material is made by mechanical ball milling of Te and Ru co-doped FeS2 material, sulfide electrolyte, and conductive carbon. The addition of conductive carbon can improve the electronic conductivity of the composite material; the addition of sulfide electrolyte can provide contact between particles and improve the ion transmission inside the composite positive electrode to the positive electrode / electrolyte interface; the composite positive electrode prepared by the present invention has a capacity of 508 mAhg after 588 cycles. -1 It also has super cycle stability with a capacity retention rate of 91%, and its rate performance is also improved.
[0026] 4. When preparing Te and Ru co-doped FeS2 composite positive electrode materials, a combination of ball milling and tumbling is used. The tumbling method can ensure that FeS2 and sulfide electrolytes are in contact with the ball milling media beads to the greatest extent, thereby improving the efficiency and scale of the mixing of the two. Ball milling can provide high-energy impact to destroy the gradient distribution of components caused by the physical polymerization of the three components. This tumbling method may result in the conductive carbon not being evenly distributed inside and outside. The combination of the two can make the conductive carbon fully distributed inside and outside the composite material. In general, pre-mixing and then mixing with conductive carbon is more sufficient, which is conducive to the uniform distribution of electrolytes and conductive carbon in the active material, and ensures the effective transmission of ions and electrons inside the composite positive electrode. At the same time, step-by-step mixing provides an opportunity to controllably monitor the particle size changes and mixing degree of the particles, which is convenient for the whole process evaluation and design of the composite positive electrode. In the process of large-scale production practice, the output of materials obtained in different ball milling stages can be efficiently controlled to improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 The FeRu prepared in Preparation Example 1 0.5 S2T 0.5 SEM images of materials; Figure 2 It is the FeRu prepared in Comparative Example 1 0.5 S2T 0.5 SEM images of materials; Figure 3 The FeRu obtained in Preparation Example 1 0.5 S2T 0.5 XRD pattern of Figure 4 The FeRu obtained in Preparation Example 1 0.5 S2T 0.5 Raman diagram of Figure 5 is a rate performance comparison curve diagram of Example 1 and Comparative Example 1; Figure 6 1 is the first cycle charge and discharge curve diagram of Example 1 and Comparative Example 2; Figure 7 It is a long cycle performance comparison curve of the composite positive electrodes of Example 1 and Comparative Examples 3, 6, 7 and 8 using different doping amounts and different ball milling preparation methods; Figure 8 It is a long cycle performance comparison curve diagram of Example 1 and Comparative Examples 4 and 5; Fig. 9 is the first cycle charge and discharge curve diagram of Example 1-3; Fig.10It is the first cycle charge and discharge curve diagram of comparative example 2 and comparative example 4. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0029] In the following embodiments and comparative examples: The conductive agent used is VGCF; the protective gas is argon.
[0030] Preparation Example 1 FeRu 0.5 S2T 0.5 Preparation of materials 1. In a glove box, mix ferrous sulfide powder (FeS2) and tellurium ruthenium powder (Te&Ru) in a molar ratio of 1: (0.5:0.5). Use a mortar and pestle to pre-grind the mixed powder for 30 minutes to ensure that the two powders are fully mixed; Among them, tellurium ruthenium powder (Te&Ru) is a mixed powder of tellurium powder and ruthenium powder in a molar ratio of 1:1; the molar ratio of ferrous sulfide powder (FeS2) and tellurium ruthenium powder (Te&Ru) is 1:1.
[0031] 2. The premixed powder is transferred to a zirconia ball milling jar, and a certain amount of zirconia ball milling beads are added. Mechanical ball milling is performed using a planetary ball mill with a ball-to-material ratio of 5:1, a ball milling speed of 450 rpm, and a ball milling time of 18 hours.
[0032] 3. After the ball milling is completed, the ball milling beads and the material are separated, and then the material is placed in a closed container for calcination. The calcination is carried out in a tube furnace, the temperature is controlled at 900°C, and the calcination time is 11 hours. After the calcination is completed, the mixture is allowed to cool naturally to room temperature to complete the entire preparation process.
[0033] Figure 1 FeRu prepared in Example 1 0.5 S2T 0.5 SEM image of the material; this image shows FeRu 0.5 S2T 0.5 The particle distribution is uniform and the crystal particle size is small and uniform, indicating that the use of pre-grinding and ball milling has a positive effect on the material size distribution and particle size.
[0034] Figure 3 FeRu obtained in Preparation Example 1 0.5 S2T 0.5XRD pattern of FeRu 0.5 S2T 0.5 The substance does not contain Te and Ru elements, and the synthesized material has high purity. Judging from the sharpness of the peak, the substance has good crystallinity.
[0035] Figure 4 The FeRu obtained in Preparation Example 1 0.5 S2T 0.5 Raman map; this map can show that the prepared material has the target chemical bonds and no impurity peaks.
[0036] Comparative Preparation Example 1 The difference between this comparative preparation example and preparation example 1 is that there is no ball milling process, and the calcination step is directly performed after grinding for 30 minutes.
[0037] Figure 2 It is the FeRu prepared in Comparative Example 1 0.5 S2T 0.5 SEM image of the material; this image shows FeRu 0.5 S2T 0.5 The particles showed a large degree of aggregation and the particle size distribution was dispersed, indicating that the precursor raw materials were not fully mixed, resulting in an unsatisfactory crystal formation process.
[0038] Comparative Preparation Example 2 The difference between this comparative preparation example and preparation example 1 is that the molar ratio of ferrous sulfide powder (FeS2) to tellurium ruthenium powder (Te&Ru) is 2:(0.5:0.5). The remaining steps are the same to obtain FeRu 0.25 S2T 0.25 .
[0039] Comparative Preparation Example 3 The difference between this comparative preparation example and preparation example 1 is that in step 1, tellurium ruthenium powder (Te&Ru) is replaced by single ruthenium powder, and the molar ratio of ferrous sulfide powder (FeS2) and ruthenium powder (Ru) is 1:1. The remaining steps are the same to obtain FeRuS2.
[0040] Comparative Preparation Example 4 The difference between this comparative preparation example and preparation example 1 is that in step 1, tellurium ruthenium powder (Te&Ru) is replaced by ruthenium dioxide, and the remaining steps are the same to obtain FeS2·RuO2.
[0041] Example 1 FeRu for sulfide-based all-solid-state lithium batteries 0.5 S2T 0.5 Preparation of composite cathode materials Step 1. According to the ball-to-material ratio of 3:1, weigh the zirconium oxide beads into the zirconium oxide ball mill, dry them in a 60°C oven for four hours, and then transfer them to an argon glove box (the water content of the argon in the glove box is less than 1 ppm, and the oxygen content is less than 1 ppm); 400 mgFe 0.5 Ru 0.5 STe (prepared in Preparation Example 1) and 400 mg Li 5.5 PS 4.5 Cl 1.5 Add to the ball mill and seal with insulating tape; perform intermittent rolling milling at a speed of 200 rpm (rolling for 1 hour; stop for 10 minutes; 8 times in total); after rolling milling, transfer the ball mill to the glove box and separate the ball and material; Step 2: Add 200 mg of VGCF and the material separated in step 1 to a mortar for premixing, and then transfer to a ball mill for intermittent ball milling at a speed of 450 rpm with a ball (zirconia bead) material ratio of 5:1 (intermittent ball milling method: ball milling for 30 minutes; stop for 5 minutes, a total of 20 times). After ball milling, separate the ball material to obtain FeRu 0.5 S2T 0.5 Composite positive electrode.
[0042] Example 2 Step 1. According to the ball-to-material ratio of 3:1, weigh the zirconium oxide beads into the zirconium oxide ball mill, dry them in a 60°C oven for four hours, and then transfer them to an argon glove box (the water content of the argon in the glove box is less than 1 ppm, and the oxygen content is less than 1 ppm); 400 mgFe 0.5 Ru 0.5 STe (prepared in Preparation Example 1) and 400 mg Li 10 GeP2S 12 Add to the ball mill jar and seal with insulating tape; intermittently roll mill at a speed of 200 rpm (roll for 30 minutes; stop for 5 minutes; a total of 20 times); after rolling, transfer the ball mill jar to the glove box and separate the ball and material; Step 2: Add 200 mg VGCF and the material separated in step 1 to a mortar for premixing, then transfer to a ball mill and perform intermittent ball milling at a speed of 450 rpm with a ball (zirconia bead) material ratio of 5:1 (intermittent ball milling method: ball milling for 30 minutes; stop for 5 minutes, a total of 20 times). After ball milling, separate the ball material to obtain FeRu 0.5 S2T 0.5 Composite positive electrode.
[0043] Example 3 Step 1. According to the ball-to-material ratio of 3:1, weigh the zirconium oxide beads into the zirconium oxide ball mill, dry them in a 60°C oven for four hours, and then transfer them to an argon glove box (the water content of the argon in the glove box is less than 1 ppm, and the oxygen content is less than 1 ppm); 400 mgFe 0.5 Ru 0.5 STe (prepared in Preparation Example 1) and 400 mg 80Li2S·20P2S5 were added to a ball mill, which was sealed with insulating tape; intermittent milling was performed at a speed of 200 rpm (wherein the intermittent milling method was: milling for 30 min; stopping for 5 min, for a total of 20 times); after milling, the ball mill was transferred to a glove box and the ball and material were separated; Step 2: Add 200 mg of VGCF and the material separated in step 1 to a mortar for premixing, and then transfer to a ball mill for intermittent ball milling at a speed of 450 rpm with a ball (zirconia bead) material ratio of 5:1 (intermittent ball milling method: ball milling for 30 minutes; stop for 5 minutes, a total of 20 times). After ball milling, separate the ball material to obtain FeRu 0.5 S2T 0.5 Composite positive electrode.
[0044] Comparative Example 1 The difference between this comparative example and Example 1 is that: in step 1, FeRu 0.5 S2T 0.5 Replaced with FeRu prepared in Comparative Preparation Example 1 0.5 S2T 0.5 .
[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that: in step 1, FeRu 0.5 S2T 0.5 Replace with commercial micron FeS2 (Iron disulfide|1309-36-0|Adamas|99.99%|RG|), and the rest of the operation steps are the same.
[0046] The other steps are consistent with those in Example 1.
[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that: in step 1, FeRu 0.5 S2T 0.5 Replaced with FeRu prepared in Comparative Preparation Example 2 0.25 S2T 0.25 .
[0048] The other steps are consistent with those in Example 1.
[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that: in step 1, FeRu 0.5 S2T 0.5 Replaced with FeRuS2 prepared in Comparative Preparation Example 3.
[0050] The other steps are consistent with those in Example 1.
[0051] Comparative Example 5 The difference between this comparative example and Example 1 is that: in step 1, FeRu 0.5 S2T 0.5 Replaced with FeS2·RuO2 prepared in Comparative Preparation Example 4.
[0052] Comparative Example 6 The difference between this comparative example and Example 1 is that FeRu 0.5 S2T 0.5 , Li 5.5 PS 4.5 Cl 1.5、 VGCF is mixed at the same time and tumbled once.
[0053] According to the ball-to-material ratio of 3:1, zirconia beads were weighed into a zirconia ball mill, dried in an oven at 60°C for four hours, and then transferred to an argon glove box (the water content of the argon in the glove box was less than 1 ppm, and the oxygen content was less than 1 ppm); 400 mg FeRu 0.5 S2T 0.5 (Preparation Example 1) and 400 mg Li 5.5 PS 4.5 Cl 1.5 Add 200 mg VGCF into the ball mill and seal it with insulating tape; intermittently roll mill for 9 h 20 min at a speed of 200 rpm (intermittent ball milling method: roll mill for 30 min; stop for 5 min); after rolling, transfer the ball mill to the glove box and separate the ball and material to obtain FeRu 0.5 S2T 0.5 Composite positive electrode.
[0054] Comparative Example 7 The difference between this comparative example and Example 1 is that FeRu 0.5 S2T 0.5 , Li 5.5 PS 4.5 Cl 1.5 , VGCF are mixed simultaneously and ball milled once.
[0055] According to the ball-to-material ratio of 5:1, zirconia beads were weighed into a zirconia ball mill, dried in an oven at 60°C for four hours, and then transferred to an argon glove box (the water content of the argon in the glove box was less than 1 ppm, and the oxygen content was less than 1 ppm); 400 mg FeRu0.5 S2T 0.5 (Preparation Example 1) and 400 mg Li 5.5 PS 4.5 Cl 1.5 Add it together with 200 mg VGCF into a ball mill and seal it with insulating tape; intermittently ball mill for 9 h 20 min at a rotation speed of 450 rpm (intermittent ball milling method: ball milling for 30 min; stop for 5 min); after the ball milling is completed, transfer the ball mill to a glove box and separate the ball and material to obtain FeRu0.5S2Te0.5.
[0056] Comparative Example 8 The difference between this comparative example and Example 1 is that in step 1 and step 2, the mixing method adopts a continuous rolling / ball milling method, that is, continuous rolling / ball milling for 8 hours.
[0057] Application performance testing: Test method: 10 mg of the composite positive electrode and 100 mg of the electrolyte (Li 5.5 PS 4.5 Cl 1.5 ) are pressed into sheets in a pressure mold and assembled into a full battery with a lithium-indium alloy negative electrode. The charge and discharge rate tested is 0.025 C-1 C, and the charge and discharge cut-off voltage is relative to LiIn / Li + The charge and discharge capacities of the present invention refer to the positive electrode FeRu 0.5 S2T 0.5 / FeS2 / FeRuS2 / FeS2·RuO2 / FeRu 0.25 S2T 0.25 Specific capacity calculated based on composite active materials.
[0058] Figure 5 The rate performance comparison curve of Example 1 and Comparative Example 1 shows that the composite positive electrode of Example 1 has advantages in capacity and rate over Comparative Example 1. The main reason is that FeRu 0.5 S2T 0.5 The difference in the crystallinity and crystal particle distribution of the material. Smaller crystals can be in good contact with the composite cathode components, and more uniform particle distribution can alleviate the instability of the crystal phase, so the former can release more energy and have higher stability at higher rates.
[0059] Figure 6 The first cycle charge and discharge curves of Example 1 and Comparative Example 2 are shown in the figure. 0.5 S2T 0.5It has a wider electrochemical window, so it can have a higher first-cycle discharge capacity than FeS2 (0.38-2.38V) in the voltage window of 0.1-3V.
[0060] Figure 7 It is a comparative curve diagram of the long cycle performance of the composite positive electrode materials using different doping amounts and different ball milling preparation methods in Example 1 and Comparative Examples 3, 6, 7 and 8. The figure shows that the co-doping modification of Te and Ru elements and the preparation method of the composite positive electrode also directly and indirectly affect the overall stability of the composite positive electrode.
[0061] Figure 8 The long cycle performance comparison curve of Example 1 and Comparative Examples 4 and 5 shows that the doping of Te and Ru elements does not affect the structure of the crystal, and thus can maximize the capacity of the active material, while the doping of single ruthenium element and ruthenium oxide destroys the structure of the FeS2 matrix and cannot be doped, resulting in impaired capacity. At the same time, the long cycle performance comparison curve of Comparative Examples 4 and 5 can indirectly reflect that the effect of single element doping is better than that of oxide doping.
[0062] Fig. 9 It is the first cycle charge and discharge curve diagram of Example 1-3. It can be seen that the modified positive electrode is compatible with the sulfide solid electrolyte. The three electrolytes play almost the same excellent transmission effect in the composite positive electrode to ensure the maximum realization of capacity.
[0063] Fig.10 It is the first cycle charge and discharge curve diagram of comparative example 2 and comparative example 4. It can be seen that the introduction of Ru element doping in FeS2 can realize the above-mentioned role of Ru in catalyzing electrochemical redox reactions, thereby improving the charge and discharge efficiency of the battery (discharge specific capacity / charge specific capacity). It can be seen from the figure that the charge and discharge efficiency of FeRuS2 is much higher than that of FeS2.
[0064] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing Te and Ru co-doped FeS2 material, characterized in that: The steps include: S1. Premixing ferrous sulfide powder and tellurium ruthenium powder under inert gas to obtain a premix; the molar ratio of the ferrous sulfide powder to the tellurium ruthenium powder is 1-1.8:1; the tellurium ruthenium powder is a mixed powder of tellurium powder and ruthenium powder; S2, ball milling the premix; S3. The ball-milled material is calcined, and the calcined product is cooled to ambient temperature to obtain the Te and Ru co-doped FeS2 material.
2. The preparation method according to claim 1, characterized in that: In the tellurium ruthenium powder, the molar ratio of tellurium powder to ruthenium powder is 1:2-2:
1.
3. The preparation method according to claim 1, characterized in that: Mechanical ball milling was performed using a planetary ball mill; the ball-to-material ratio was 3-5:1, the ball milling conditions were 350-450 rpm, and the ball milling time was 18-24 h.
4. The preparation method according to claim 1, characterized in that: In step S3, the calcination temperature is 800° C. to 950° C., and the calcination time is 10 hours to 12 hours.
5. A Te and Ru co-doped FeS2 material prepared by the preparation method as described in any one of claims 1 to 4.
6. A method for preparing a Te and Ru co-doped FeS2 composite positive electrode material, characterized in that: The steps include: Step 1, under a protective atmosphere, mixing the Te and Ru co-doped FeS2 material as claimed in claim 5 with a sulfide electrolyte in proportion and rolling; Step 2: Continue to add conductive carbon to the material of step 1 and further ball mill to obtain the Te and Ru co-doped FeS2 composite positive electrode material.
7. The method for preparing the Te and Ru co-doped FeS2 composite positive electrode material according to claim 6, characterized in that: In step 1, the rolling conditions are: ball-to-material ratio 2:1-5:1; rotation speed 200-500rpm; rolling method is intermittent rolling, grinding for 1-2h each time, and stopping for 5-10min; a total of 8-10 times of rolling.
8. The method for preparing the Te and Ru co-doped FeS2 composite positive electrode material according to claim 6, characterized in that: In step 2, the ball milling conditions are: ball-to-material ratio 2:1-5:1; rotation speed 300-500 rpm; intermittent ball milling; each ball milling time is 30-60 minutes, and then stop for 5-10 minutes; a total of 10-20 hours.
9. The method for preparing the Te and Ru co-doped FeS2 composite positive electrode material according to claim 6, characterized in that: The mass ratio of the Te and Ru co-doped FeS2 material, sulfide electrolyte, and conductive carbon is 40~50:40~50:10~20.
10. A Te and Ru co-doped FeS2 composite positive electrode material prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Iron-containing superconductive substance
CN102203005A
Method for preparing anode material of lithium ion battery
CN102751489A
Nanometer FeS2 for sulfide all-solid-state lithium battery and composite positive electrode material of nanometer FeS2
CN118458834A
SUPERCONDUCTING METHOD FOR FeTe1-xSx COMPOUND SYNTHESIZED BY SOLID PHASE REACTION
JP2012148913A
Positive electrode comprising additive material and metal sulfide, fabrication method thereof, and battery comprising the positive electrode
KR1020100133879A